Palabra de fin. Muerte y escritura en el Quijote - Peñalver Alhambra, Luís (Escritura e Imagen, 2006)
Don Quixote, as the modern man, is a choice of himself, a choice that is made above all by means of the language: it is necessary to name the things again so that the things will change. The knight decides to reinvent himself by copying his models. The model of the real is provided by the Book. Things are real because they are part of the words and more exactly, part of the written words. But if in this way he turns the book into life with his death life will end up being turned into a book. Don Quixote dies but not the collective Quixote, not the Quixote of the writing that is born again with each reader.